Analisis Ketergantungan China-Sri Lanka dalam Proyek Pembangunan Pelabuhan Hambantota Tahun 2007-2017 - Nurjayanti, Vivi Ariesta (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
The purpose of this research is that the reader can find out the problem of Sri Lanka's dependence on China in the Hambantota Port development project which ultimately ended up as a debt trap. In this research authors used qualitative research methods. And from the results of research that has been done, it is found that basically the cooperation carried out by China and Sri Lanka is a collaboration between hegemon countries and third world countries. Debt trap diplomacy itself has close links with other Chinese policies, namely the Belt and Road Initiative, this policy focuses on infrastructure development which includes the construction of railroad networks, the construction of roads to ports located in the territories of other countries and has a strategic position and will good impact for the achievement of Chinese interests in realizing the